The Beeswax Wrap / Nur Husna Rosli … [et al.] - Rosli, Nur Husna; Abu Bakar, Nurul Fatehah; Mohd Salihin, Siti Nurfarah Nabila; Zulkifli, Aisyah Asyiqin; Muhamad Rahim, Afrina Athirah (2022)
The Beeswax Wrap officially registered on the 2nd of March 2022. The company sells organic food wrap that is made of beeswax. Beeswax wrap is not only eco-friendly, but it is also much safer to use as compared to plastic food wraps that are made from chemicals and can harm the environment. Beeswax wraps are biodegradable and have built-in antibacterial protection. This will keep food fresher for a longer period of time, thus reducing food waste and preventing pollution. The business is located in Jalan Malim Jaya, Malacca. It is a strategic location to start a business since it is near the city, where there are a lot of locals and tourists from other states and overseas. There are also barely any firms or shops that sell beeswax wrap there. Locals usually have to shop online to get their hands on beeswax wrap. Ultimately, making it easier for our company to stand out and attract a lot of potential customers. Currently, The Beeswax Wrap market share is 15%. It is currently the lowest market share as compared to its competitors. Nonetheless, the price is a bit pricier than the other companies which is RM28.50. It is due to the quality of our product and the ingredients used to make it. We produce 250 units of beeswax wrap per day, and each product is carefully made and inspected before it is sold. Our target markets are based on demographic, psychographics, as well as geographic. By determining our target market, we can concentrate our efforts on the people who are most likely to purchase our products. By limiting the population, research and resources are directed at the clients who have the most revenue potential. By doing this, our company can lower our production cost, marketing cost and save resources. Lastly, our mission is to reduce the use of food plastic wrap by providing more organic and compostable food wrapping through beeswax wrap. Meanwhile, our vision is to help the community to get safer and non-chemical food wrap in Malaysia.